2012
DOI: 10.1542/peds.2011-1294
|View full text |Cite
|
Sign up to set email alerts
|

Trivalent Inactivated Influenza Vaccine Is Not Associated With Sickle Cell Crises in Children

Abstract: Background and Objectives: Children with sickle cell disease are considered at high risk for complications from influenza infection and are recommended to receive annual influenza vaccination. However, data on the safety of influenza vaccination in children with sickle cell anemia are sparse. Methods: Using a retrospective cohort of children aged 6 months to 17 years in 8 managed care organizations that comprise the Vaccine S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
(11 reference statements)
1
15
0
Order By: Relevance
“…Influenza vaccines are generally considered safe among individuals with sickle cell disease; however, one study suggested a 7- to 9-fold increased risk of hospitalization for sickle cell anemia after administration of trivalent inactivated vaccine [61]. Follow-up studies by the same group did not find increased hospitalizations for sickle cell crises in adults [62] or children [63] after influenza vaccination. No vaccine effectiveness or efficacy studies among persons with sickle cell disease have been conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Influenza vaccines are generally considered safe among individuals with sickle cell disease; however, one study suggested a 7- to 9-fold increased risk of hospitalization for sickle cell anemia after administration of trivalent inactivated vaccine [61]. Follow-up studies by the same group did not find increased hospitalizations for sickle cell crises in adults [62] or children [63] after influenza vaccination. No vaccine effectiveness or efficacy studies among persons with sickle cell disease have been conducted.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 The mechanism underlying this enhanced risk is incompletely understood, but may involve influenza: 1) compromising respiratory tract mucosal immunity; 36 2) causing acute chest syndrome; 37 and 3) provoking fever which results in precautionary admission to rule out bacterial sepsis. Fortunately, influenza immunization is both safe 38,39 and immunogenic 39,40 in children with SCD, and is efficacious in children generally. 8 Influenza immunization has been recommended for children with SCD by the Advisory Committee on Immunization Practices of the CDC since 1978, 41 and is now recommended for all children over 6 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Even when a vaccine is routinely administered as part of the standard vaccination schedule, such as is the case with the trivalent inactivated influenza (TIV) vaccine, controversy may arise pertaining to its safety in people with uncommon diseases. Indeed, recent retrospective studies using the vaccine safety datalink project have indicated that the TIV vaccine is not associated with hospitalization in children or adults with SCD ( 10 , 11 ); however, a previous report by this group had shown that people with SCD had more frequent fever or pain episodes resulting in an inpatient visit within two weeks of influenza vaccination than control subjects ( 12 ). To our knowledge, no published prospective studies have been conducted in humans or mice to definitively determine if vaccination is associated with adverse effects in SCD.…”
Section: Introductionmentioning
confidence: 98%